2016
DOI: 10.1590/1807-57622015.0596
|View full text |Cite
|
Sign up to set email alerts
|

“Mata de tristeza!”: representações sociais de pessoas com vitiligo atendidas na Farmácia Universitária da Universidade Federal do Rio de Janeiro, Brasil

Abstract: Vitiligo é caracterizado por manchas brancas na pele. Na dispensação do metoxisaleno utilizado para tratá-lo, na Farmácia Universitária/UFRJ, os portadores relatavam mal-estares devido à terapia e à doença. A busca pela compreensão da experiência do adoecer conduziu este estudo que adota perspectiva teórico-metodológica socioantropológica. A apreensão da visão de mundo dos sujeitos foi captada em entrevistas entre usuários da FU/ UFRJ. A partir do diagnóstico, os sujeitos consideram o vitiligo "um castigo", se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(19 reference statements)
1
9
0
2
Order By: Relevance
“…Our results are consistent with studies dealing with implications found with dermatitis, in which the self-esteem and quality of life of people with dermatological alterations are impaired due to a sensation of transmitting a negative image to other people (Ajose, et al, 2014;Azevêdo, 2016;Correia & Bortoli, 2013;Noh, Kim, Park, Hann & Oh, 2013). Szabo and Brandão (2016) also show that the concerns of men and women having Vitiligo are related to the transfi gurations that the disease causes, and share dysfunctional beliefs that the disease makes them less attractive to their loving partners, and constitutes an impediment to obtaining one.…”
Section: Analysis Of the Stimulus "Myself"supporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with studies dealing with implications found with dermatitis, in which the self-esteem and quality of life of people with dermatological alterations are impaired due to a sensation of transmitting a negative image to other people (Ajose, et al, 2014;Azevêdo, 2016;Correia & Bortoli, 2013;Noh, Kim, Park, Hann & Oh, 2013). Szabo and Brandão (2016) also show that the concerns of men and women having Vitiligo are related to the transfi gurations that the disease causes, and share dysfunctional beliefs that the disease makes them less attractive to their loving partners, and constitutes an impediment to obtaining one.…”
Section: Analysis Of the Stimulus "Myself"supporting
confidence: 91%
“…Using the SRT dimensional approach to a holistic understanding of Vitiligo, we highlight the three solitary Brazilian studies existence, found in the national and international literature (Andrade, Ferraz, Coelho, & Pinto, 2016;Do Bú et al, 2017;Szabo & Brandão, 2016). These seek, from the realities of those affl icted by the disease, to understand the constructed and socially shared meanings developed in the face of this event.…”
Section: Estructura Representacional Del Vitiligo: Marcas Que No Se Rmentioning
confidence: 99%
“…Prejudice towards people with Vitiligo has been widely indicated in studies as one of these attitudes, showing, from the perspective of those who have the illness, its negative implications and difficulties when establishing relationships in social interactions (e.g., Do Bú & Coutinho, 2019; Do Bú et al, 2017, 2018; Pahwa et al, 2013; Szabo & Brandão, 2016). Nevertheless, to the best of our knowledge, there is no validated instrument to measure prejudice against this population.…”
Section: Prejudice Towards People With Vitiligomentioning
confidence: 99%
“…Efeitos adversos podem ocorrer como a atrofia epidérmica, acne induzida por corticoides, equimoses, estrias e rosácea, sendo que os pacientes possuem maior risco de atrofia quando usam corticoides mais potentes. Lesões localizadas na face e pescoço devem ser tratadas com corticoides de média potência, já no restante do corpo utiliza-se corticoides de alta potência (SZABO; BRANDÃO, 2016).…”
Section: Tratamento Do Vitiligounclassified